2021
DOI: 10.3390/ijms222212419
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia, Vascular Disease and Cognitive Dysfunction in Diabetes: Insights from Text Mining-Based Reconstruction and Bioinformatics Analysis of the Gene Networks

Abstract: Hypoglycemia has been recognized as a risk factor for diabetic vascular complications and cognitive decline, but the molecular mechanisms of the effect of hypoglycemia on target organs are not fully understood. In this work, gene networks of hypoglycemia and cardiovascular disease, diabetic retinopathy, diabetic nephropathy, diabetic neuropathy, cognitive decline, and Alzheimer’s disease were reconstructed using ANDSystem, a text-mining-based tool. The gene network of hypoglycemia included 141 genes and 2467 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 111 publications
(133 reference statements)
0
9
0
Order By: Relevance
“…Hypoglycemia is the most common acute complication associated with the treatment of diabetes and has a strong impact on brain metabolism and function [ 70 , 71 , 72 ]. Hippocampal homogenate was used as a source of brain mitochondria by He et al who reported that recurrent hypoglycemia in diabetic rats caused a drop in NADH-linked OXPHOS, OXPHOS capacity, ET capacity and succinate-dependent ET capacity compared with diabetic controls without recurrent drops in glycemia.…”
Section: Effects Of Diabetes On Mitochondrial Respiration In Animal S...mentioning
confidence: 99%
“…Hypoglycemia is the most common acute complication associated with the treatment of diabetes and has a strong impact on brain metabolism and function [ 70 , 71 , 72 ]. Hippocampal homogenate was used as a source of brain mitochondria by He et al who reported that recurrent hypoglycemia in diabetic rats caused a drop in NADH-linked OXPHOS, OXPHOS capacity, ET capacity and succinate-dependent ET capacity compared with diabetic controls without recurrent drops in glycemia.…”
Section: Effects Of Diabetes On Mitochondrial Respiration In Animal S...mentioning
confidence: 99%
“…The CTS is calculated as a number of neighbors of a particular node (molecule) in a network divided by the number of all neighbors of the node in the global human gene network of the ANDSystem. A higher CTS value means that a node is closely and specifically related to a studied network [24,[26][27][28]. The highest crosstalk specificity (CTS) values (Table S3) were demonstrated by uncoupling protein 2 (UCP2), hydroxisteroid 11-beta dehydrohenase-1 (HSD11B1), interleukin-19 (IL19), fatty acid binding protein 1 (FABP1), pyroglutamylated RFamide peptide (QRFP), resistin (RETN), solute carrier family 2 member 2 (SLC2A2), leptin receptor overlapping transport (LEPROT), endothelial cell-specific molecule 1 (ESM1), and cholecystokinin (CCK) genes.…”
Section: Network Associated With Hyperglycemiamentioning
confidence: 99%
“…In this work, we operated on gene networks associated with cardiovascular disease (CVD), diabetic nephropathy, diabetic retinopathy, and diabetic neuropathy that have been reconstructed and described previously [27,28]. These networks include 494, 685, 424, and 130 genes/proteins, respectively (Table S5).…”
Section: Network Associated With Diabetic Complications Insulin Resis...mentioning
confidence: 99%
See 1 more Smart Citation
“…Background: High glucose variability (GV) is recognized as a contributor for diabetic microvascular and macrovascular complications, including diabetic retinopathy, chronic kidney disease, diabetic neuropathy, and macrovascular disease [1][2][3]. The results of numerous studies have pointed to the role of endothelial dysfunction in the development of these complications [1,4].…”
mentioning
confidence: 99%